Pengaruh Social Demography, Financial Confidence, Financial Attitude, Dan Financial Knowledge Terhadap Financial Management Behaviour Petani Di Kecamatan Purwoharjo Kabupaten Banyuwangi - Ainun Binti Saiful,; Nadia Asandimitra Haryono,; Trias Madanika Kusumaningrum,; Yuyun Isbanah,; Erlangga Frisky Novarenza, (Seminar Nasional Manajemen, 2025)
This study aims to determine how socio-demographics, beliefs, attitudes, and financial knowledge affect farmers' financial management behavior in Purwoharjo District, Banyuwangi Regency. The quantitative method used in this study is SmartPLS-based Structural Equation Modeling (SEM). 100 purposively selected farmers were used as samples. Theory of Action Planning (TPB) is the most commonly used. The findings of the study indicate that financial confidence and financial literacy have a positive and significant impact on financial management behavior; in contrast, socio-demographic factors and financial behavior do not show a significant impact. Based on the results of the study, the four independent variables in this model explain variations in financial management behavior. One interesting result of this study is that having a high level of self-confidence and financial knowledge does not always lead to good financial management behavior; this may be due to overconfidence or a mismatch between knowledge and practice. This study suggests that there is a need for more practical methods to improve healthy financial behavior for farmers and provides important implications for the development of financial education interventions.